Pengaruh Promosi Dan Service Quality Dalam Meningkatkan Penjualan Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Aplikasi Shopee (Studi Kasus Mahasiswa Upi Yptk Khusus Manajemen) - Reza Algeri; Emil Salim; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to determine the extent of the influence of Promotion and Service Quality in increasing Sales with Consumer Satisfaction as an intervening variable on the Shopee Application (Case Study of Management Students at UPI “YPTK” Padang). This research uses a quantitative approach and the sampling technique used is purposive sampling with a total sample of 96 respondents, namely Management students of UPI “YPTK” Padang who use the Shopee application. Data analysis was performed using the SmartPLS 3.0 version software. The results of the study indicate that: Promotion has a significant effect on Consumer Satisfaction on the Shopee Application. Service Quality has a significant effect on Consumer Satisfaction on the Shopee Application. Promotion has a significant effect on Sales on the Shopee Application. Service Quality has a significant effect on Sales on the Shopee Application. Consumer Satisfaction has a significant effect on Sales on the Shopee Application. Consumer Satisfaction is able to mediate the effect of Promotion on Sales on the Shopee Application. Consumer Satisfaction is able to mediate the effect of Service Quality on Sales on the Shopee Application.